Sarcasm in Indonesian Television Reality Comedy Show, Lapor Pak! - Nazirotun Nikmah; Ainur Rafika Azni; Immanuela Calista (CV. Ulil Albab Corp, 2026)
The objectives of this research are to examine the forms, methods, and functions of sarcasm in the Indonesian TV reality comedy show Lapor Pak!. This research is qualitative and descriptive. This research is qualitative and descriptive. The sample of this research sarcastic dialogues from selected episodes. The data were gathered by observing episodes and identifying sarcasm based on using Elisabeth Champ’s (2011) study and were analysed using content analysis. The findings shows that illocutionary and lexical sarcasm are the most common, serving humor and social criticism